BIOEFFICACY OF LAMBDA CYHALOTHRIN 4.9 C AGAINST CHILLI THRIPS & FRUIT BORERS - BISWAJIT PATRA,; SK. F. ALAM,; A. SAMANTA,; MOULITA CHATTERJEE, (The Bioscan, 2015)
Lambda cyhalothrin 4.9 CS was tested in the field of Sagar Island of Sundarban, West Bengal at four dose levels (12.5, 15, 20 and 25 g a.i/ha) against the chilli thrips and chilli fruit borer in pre-kharif season of two consecutive years, 2010 and 2011. Two standard check fipronil 5% SC @ 50g a.i/ha and spinosad 48 SC @ 80 g a.i/ha along with an untreated check were also taken for comparison. Lowest average score of thrips (0.75 and 1.19 in two years) were recorded in lambda cyhalothrin 4.9 CS @ 25 g a.i./ha treated plots. Average no. of Spodoptera larvae per plant were also lowest (1.94 & 2.01) in this treatment. The highest yield was recorded from lambda cyhalothrin 4.9 CS @ 25 g a.i./ha treated plots (62.33 and 61.06 q/ha). Lambda cyhalothrin 4.9 CS @ 25 g a.i./ ha reduces the population of Menochilus sp. to the tune of 20.82% and 0.84 % while population of Chrysoperla sp. was reduced to 9.03% and 1.89% only in the respective year of studies.